The evaluation of malignancies in Turkish primary immunodeficiency patients; a multicenter study - ÖZEN, AHMET OĞUZHAN; BARIŞ, SAFA (WILEY, 2020)
Background There are no data regarding the prevalence of malignancies in patients with primary immunodeficiency (PID) in Turkey. Along with the prevalence of malignancy, we aimed to present the types of malignancy and define the underlying immune deficiency of the patients. Method Between the years 1992 and 2018, from five tertiary immunology clinics, fifty-nine patients with PID who developed malignancy were included. All patients were evaluated for demographics, clinical features, and prognosis. Results The prevalence of malignancy in our cohort was detected as 0.9% (59/6392). The male-to-female ratio was 1.8 (38/21), and the median age of patients was 14 years (range: 1.5-51). The median age at diagnosis of malignancy was 10 years (range: 1.5-51). Ataxia-telangiectasia was the most frequent PID in patients with malignancy (n = 19, 32.2%), and non-Hodgkin lymphoma was the most common malignancy (n = 32, 51.6%). The rate of malignancy in DOCK8 deficiency (n = 7/43, 16.3%) was higher than AT (n = 19/193, 9.8%), Wiskott-Aldrich syndrome (n = 2/22, 9.1%), and common variable immunodeficiency (n = 11/205, 5.4%). EBV quantitative PCR was positive in 16 out of 53 patients (30.2%). Three patients had secondary malignancies. Remission was achieved in 26 patients (44.1%). However, 31 patients (52.5%) died. Two patients (3.4%) are still on chemotherapy. Conclusion This study is the largest cohort investigating the association of malignancy in patients with PID in Turkey. While lymphoid malignancies were the most common malignancy and observed more frequently in AT patients, the risk for malignancy was higher in patients with DOCK8 deficiency compared to AT.
Keywords: ataxia-telangiectasia; cancer; DOCK8 deficiency; lymphoma; malignancy; non-Hodgkin lymphoma; primary immunodeficiency; CANCER INCIDENCE; ATAXIA-TELANGIECTASIA; LYMPHOMA; DISEASES; PATHOPHYSIOLOGY; SECONDARY; CHILDREN; GENE